IDENTIFIKASI FORMALIN PADA IKAN ASIN YANG DIJUAL DI KAWASAN PANTAI TELUK PENYU KABUPATEN CILACAP - Mulasari, Surahma Asti (Universitas Ahmad Dahlan, 2016)
Background: Food additives is a substance or mixture inggridients which is not main inggridient, but it added intentionally into foods to improve the nature and form of foods. Regulation of the Minister of Health No.722/Menkes/Per/IX/88 and No.1168/Menkes/PER/X/ 1999 provides supplemental food ingredients banned in food specially added formaldehyde. The observation of the study showed characteristics of salted fish identified dormalin. The purpose of this research is to know the content of formaline in salt fish which is sold in Teluk Penyu Beach area Cilacap regency.Methods: The study was descriptive qualitative laboratory approach. The primary data obtained from laboratory tests on salt fish and interview with trader in Teluk Penyu Beach Cilacap regency.Results: (1) The results of salted fish were examined as many as 13 samples, one sample of dried fish (7.69%) were identified containing formaldehyde (2) The level of knowledge salted fish traders in the Teluk Penyu Beach area Cilacap regency is said to be quite low (3) Attitude salted fish traders in the Teluk Penyu Beach area Cilacap regency against the use of formaldehyde in salted fish is good enough (4) Characteristics of salted fish that contain formaldehyde, which hold for months, net damn bright color, no smell of salted fish, and no files (5) Origin salted fish mostly derived from the manufacturer of the coast it self and from outside the region such as West Java Cilacap.Conclusions: Based on the results of laboratory tests that are sold salted fish in Teluk Penyu Beach area Cilacap regency there is a kind of salt fish one sample were identified containing formaldehyde.Â Keywords: Formalin, Salt fish